Taxation of non-renewable natural resources: what are the key issues? - Christian von Haldenwang (Deutsches Institut für Entwicklungspolitik (DIE), 2011)
Financing for development requires developing countries to step up their domestic revenue mobilisation. Such key international players as the Organisation for Economic Co-operation and Development (OECD), G20 and International Monetary Fund (IMF) are calling on the developing countries to increase their tax collection. A major issue in this context is the taxation of non-renewable natural resources. Recent DIE publications suggest that many low-income and lower-middle-income countries may be failing to tap the full revenue potential of these resources. Public opinion in resource-rich countries is pressing for the renegotiation of investment agreements and tax regimes in the light of soaring commodity prices. As extractive industries are characterised by a unique combination of properties, governments should treat them differently from the rest of the economy. From the perspective of sustainable asset management,the declining stock of finite resources should be offset by investments in produced capital so that a society's total wealth and future welfare may be preserved.This is known as “Hartwick's rule”. Hartwick's rule underestimates the necessary investments in produced capital because it does not consider negative externalities arising from substantial environmental degradation as a consequence of resource extraction. A broader concept of sustainability would take account of these externalities, including compensatory payments, for instance. Most countries regard sub-soil assets as the state's inalienable property. Companies should therefore pay a fee (royalty) for the right to exploit deposits owned by the public. Extractive industries often generate high benefits or rents , either in the longer term (owing to market entry barriers encountered by new firms) or the short term (in the form of windfall profits due to global price hikes). Some of these rents are appropriated by the state, which poses challenges in terms of revenue volatility, economic development and governance. International firms usually play an important role in the extractive sector, since they are key holders of capital and technical expertise. Further, they are often liable to tax in their own countries, exposing them to the risk of double taxation. Finally, extractive activities require high initial investments (“sunk costs”) in exploration and development and have long production periods. Their profitability tends to be uncertain at the beginning, and it can be quite difficult to determine the actual rent to be taxed later on. These arguments indicate that taxing non-renewables is more complex than may appear at first glance. Governments must take account of a number of technicalities. More importantly, however, taxing non-renewables is a highly political matter, involving powerful domestic as well as international actors, in both the private and the public sector. A key government resource in this context is the credibility that arises where the rules and regulations governing the sector are clear and the funds collected are used transparently in the common interest. If these conditions are not met, public revenue from extractive industries may be a curse rather than a blessing.
Keywords: 330